1951
DOI: 10.1103/physrev.82.83
|View full text |Cite
|
Sign up to set email alerts
|

The Infrared Spectrum of Active Nitrogen

Abstract: The equations can be simplified by the introduction of two new parameters:.6 A = f dxp{x)e-™<-xa \ 0=0(6, a)- J aIn terms of these, Eqs. (28) and (29) become R (b) = Ma)e ie + L(a)Ae ie , Mb) = L(a)e-ie +R(a)A*e-i°. (30) (31) (32)B is the phase shift per cell given by the ordinary WBK method. | A | 2 is the probability that the particle changes its direction of motion in going through one cell.Floquet's theorem tell us that the solutions to the wave equation for a periodic potential can always be w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1952
1952
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…This theory was based on analogous processes that were thought to occur in the emissioil of the spectrum of the night slry, and on the very large energies transferred to metal foils in some experiments made by Lord Rayleigh (54). I t has since been found that the interpretation of the atmospheric spectrum in terms of Nz+ was wrong (7) and that Rayleigh's results were due to bombardment by electrons from the exciting discharge (2). Mitra has therefore suggested recently (45) that the activity of active nitrogen is due to nitrogen atoms.…”
Section: Charged Particles As Actioe Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory was based on analogous processes that were thought to occur in the emissioil of the spectrum of the night slry, and on the very large energies transferred to metal foils in some experiments made by Lord Rayleigh (54). I t has since been found that the interpretation of the atmospheric spectrum in terms of Nz+ was wrong (7) and that Rayleigh's results were due to bombardment by electrons from the exciting discharge (2). Mitra has therefore suggested recently (45) that the activity of active nitrogen is due to nitrogen atoms.…”
Section: Charged Particles As Actioe Speciesmentioning
confidence: 99%
“…represent ethylene and acetylene in electronically excited triplet states and N.C2Hd is a collisio~l complex. From quenchi~lg experiments with excited metal atoms, reaction [7] is known to occur when the excitation energy is sufficiently high and it has already been pointed out (41) that this is a good example of spin con~ervation. ?~ Reaction [6] would have to compete with the energetically more favorable reaction Both reactions [6] ancl [9] are spin-allowed.…”
mentioning
confidence: 99%